PHYSICOCHEMICAL PROPERTIES AND FATTY ACID COMPOSITION OF SHEA BUTTER FROM TAMALE, NORTHERN GHANA - Garti, H.; Agbemafle, R.; Mahunu, G. K. (UDS International Journal of Development, 2019)
Shea butter is a significant source of fat in the diet of many rural dwellers in northern Ghana. It is produced from the seeds of shea tree and its suitability as dietary fat or use in cosmetic industry is greatly influenced by its physicochemical properties and fatty acid composition. The aim of this study was to determine the physicochemical properties and fatty acid profile of shea butter sold in Tamale Central market and to compare the qualities with other edible oils. The samples of shea butter were analyzed for refractive index, unsaponifiable matter, saponification, iodine, acid and peroxide values and fatty acid composition. Physicochemical properties of shea butter obtained in this study were refractive index of 1.5 at 25oC, saponification value (198 mg/KOH/g), iodine value (45.6 I2g/100g), unsaponifiable matter (19.8 %), acid value (3.2 mgKOH/g) and peroxide value (9.84 meq/kg). The predominant unsaturated fatty acids were: oleic (36.3%), linoleic (5.4%) and alpha linoleic (0.14%). The most dominant saturated fatty acids found were stearic (52.4%) and palmitic acids (3 %), arachidic (1.5%). Data suggests that shea butter sold in Tamale compared favourably with shea butter from countries within the West African sub region and Uganda and also to other edible oils. The implication of all these is that shea butter is a good cooking oil and is safe for human consumption. Keywords: Shea butter, physicochemical, fatty acid, edible oil, Vitellaria paradoxa